Role of black carbon in soil distribution of organochlorines in Lesser Himalayan Region of Pakistan. (May 2018) - Ali, Usman; Riaz, Rahat; Sweetman, Andrew James; Jones, Kevin C.; Li, Jun; Zhang, Gan; Malik, Riffat Naseem
Abstract: Black carbon and total organic carbon (TOC) along with organochlorines (OCs) were analyzed in soils from four sampling zones of Lesser Himalayan Region based on source proximity/anthropogenic influences along the altitude. CTO-375 method was used for BC analysis while OCs were analyzed by GC-MS/MS system. BC and TOC ranged between 0.16–1.77 and 6.8–41.3 mg g −1 while those of OCPs and PCBs ranged between 0.69 and 5.77 and 0.12–2.55 ng g −1, respectively. ∑ DDTs were the dominant (87.9%) among OCPs while tri- and tetra- (65.5%) homologue groups among PCBs. Hexa-PCBs, however also showed higher contribution (20.4%) in the region. Source diagnostic ratios of DDE + DDD/DDT (0.1–1.53) indicated both fresh and old input while α- HCH/ γ- HCH (0.19–2.49) showed presence of lindane in the region. Higher concentration of OCs were observed in Zone C at altitudinal range of 737–975 masl that are close to the human influences and potential sources of POPs. The results of linear regression analysis revealed potential input of BC in soil distribution of OC concentrations in the region. Graphical abstract: Image 1 Highlights: First investigation of black carbon and organochlorines in soils of Lesser Himalayan Region from Pakistan. Black carbon showed potentially important role in soil distribution of OCs. Source proximate sites were shown to be more contaminated with OCs. Recent use of DDT has observed in the region. Abstract : Black carbon's potential role in OCs distribution in soils of Lesser Himalaya.